2014
DOI: 10.3389/fpls.2014.00530
|View full text |Cite
|
Sign up to set email alerts
|

Stable oxygen isotope and flux partitioning demonstrates understory of an oak savanna contributes up to half of ecosystem carbon and water exchange

Abstract: Semi-arid ecosystems contribute about 40% to global net primary production (GPP) even though water is a major factor limiting carbon uptake. Evapotranspiration (ET) accounts for up to 95% of the water loss and in addition, vegetation can also mitigate drought effects by altering soil water distribution. Hence, partitioning of carbon and water fluxes between the soil and vegetation components is crucial to gain mechanistic understanding of vegetation effects on carbon and water cycling. However, the possible im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 78 publications
7
81
1
Order By: Relevance
“…This is in contrast to previous studies, which reported beneficial effects of plant cover on daily sums of infiltration during the same period at the onset of drought in 2011 (Dubbert et al, 2014c). However, Dubbert et al (2014c) only observed precipitation events of light intensity during the period of interest. The present study reports on high-intensity precipitation events.…”
Section: Infiltration and Distribution Of Event Watercontrasting
confidence: 87%
See 2 more Smart Citations
“…This is in contrast to previous studies, which reported beneficial effects of plant cover on daily sums of infiltration during the same period at the onset of drought in 2011 (Dubbert et al, 2014c). However, Dubbert et al (2014c) only observed precipitation events of light intensity during the period of interest. The present study reports on high-intensity precipitation events.…”
Section: Infiltration and Distribution Of Event Watercontrasting
confidence: 87%
“…Oxygen isotope compositions of soil evaporation (bare-soil plots) as well as evapotranspiration of the understorey (vegetation plots) were estimated using a mass balance approach (Dubbert et al, 2013(Dubbert et al, , 2014c:…”
Section: Cavity Ring-down Spectrometer Based Gas-exchange Flux and δ mentioning
confidence: 99%
See 1 more Smart Citation
“…Dubbert et al (2014) observed the understory vegetation contributed importantly to total ecosystem evapotranspiration of carbon with a maximum of 43%. Li et al (2010) reported that N 2 O fluxes were higher under understory removal as compared to the control without any disturbances, indicating that understory inhabited N 2 O emission in forest.…”
Section: Influence Of Understory On the Mercury Flux: Experimentsmentioning
confidence: 96%
“…Understory was an important component of forest ecosystems, while species diversity and biomass are controlling factors of soil biota, soil nutrients (Xiong et al, 2008), evapotranspiration, net primary production, net ecosystem CO 2 exchange (Dubbert et al, 2014), etc. However, the possible impact of herbaceous vegetation to mercury dynamics in forest ecosystems has been overlooked.…”
Section: Influence Of Understory On the Mercury Flux: Experimentsmentioning
confidence: 99%